Sylos Labini's Unpublished Notes on Schumpeter's Business Cycles - Carmelo Ferlito (The Quarterly Journal of Austrian Economics, 2011)
Paolo Sylos Labini (1920-2005) was the one of the most influential economists in Italy after the Second World War. After graduating in 1942, Sylos Labini won a fellowship in the USA. After an initial period in Chicago, he moved to Harvard, where he was able to attend Schumpeter's lectures from 1948 to 1950. During this period, Sylos Labini read Schumpeter's Business Cycles and decided to write down his impressions before giving them to his former professor in February 1949, who discussed them over a couple of lessons. These notes are still unpublished, and Sylos gave me a copy at our first meeting (2002), saying that it was time to publish them. This paper discusses the content of the unpublished notes, focusing on the critical aspects of Schumpeter's business cycle theory to which Labini draws attention. In the last section, I present Sylos Labini's business cycle theory, an interesting mix of Schumpeterian, Keynesian and Marxian elements.
Keywords: E32; B25; 330; Business Cycles; Schumpeter; Sylos Labini